Evaluasi Perbandingan Pembuatan Kanal Dengan Metode Konvensional Dan Metode Geosynthetic Cementitious Composite Mats (GCCM) Pada Proyek Strategis Nasional Jaringan Irigasi Baliase Di Sulawesi Selatan - Suhanda, Regi; Nasution, Mahliza (Universitas Sulawesi Tenggara, 2025)
The implementation of canal construction with an alternative method is to use Geosynthetic Cementitious Composite Mats (GCCM) which is a relatively new technology in industrial construction consisting of synthetic materials (geosynthetic) and cement concrete (cementitious). The GCCM method offers potential advantages over conventional methods, including faster construction time, lower maintenance costs, lower risk of environmental damage, and more consistent and durable channel quality. This study aims to highlight and compare the effectiveness of conventional methods and Geosynthetic Cementitious Composite Mats (GCCM) methods in canal construction. The results of the study indicate that the GCCM method has advantages in terms of structural strength, erosion resistance, and reduced environmental impacts compared to conventional methods. The results of physical tests show that GCCM significantly increases slope stability by reducing soil stoppage up to eight times compared to conventional methods. Under seepage flow conditions, slopes stabilized with GCCM remain solid without structural failure, while slopes with conventional methods experience total collapse. In terms of cost, although the price of GCCM material is higher, savings in labor and implementation duration make it more economical for large-scale projects. The results of this study can be a reference for practitioners and decision makers in choosing the right canal construction method for national strategic projects